International and national standards for the safe installation and operation of photovoltaic systems in Uzbekistan - Odiljon A. Raxmatov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: the relevance of this work lies in the fact that, against the backdrop of the active development of renewable energy sources (RES) in Uzbekistan and the increasing share of solar power plants in the country’s energy balance, the issue of standardizing solar photovoltaic systems (PVS) technologies has become strategically significant. Uzbekistan is rapidly expanding its RES capacity, forecasting an increase in their share in the total energy balance to 40% by 2025. In the context of accelerated implementation of solar technologies, ensuring the safety, durability, and efficiency of PVS plays a crucial role. International standards such as IEC 61215, IEC 61730, IEC 62446, and EN 50583 establish basic requirements for the design, testing, and operation of solar systems. Adapting these standards to national conditions has become a necessary step for the harmonious growth of the industry. Furthermore, adapting international standards to take into account national specifics supports Uzbekistan’s energy strategy aimed at achieving sustainable development goals, reducing carbon emissions, and improving energy efficiency. Thus, this article is relevant for creating a regulatory framework that promotes the safe and efficient implementation of solar technologies, strengthens energy security, and attracts international investment. Aim: the aim of this work is to analyze and adapt international standards for solar photovoltaic systems (PVS) to the conditions of Uzbekistan, taking into account national specifics and requirements. This is aimed at ensuring the safety, durability, and efficiency of PVS, harmonizing the national regulatory framework with international requirements, and creating conditions for the sustainable development of renewable energy in the country. Methods: the research methods include the analysis of international standards, their comparative evaluation with Uzbekistan's national regulations, the development of adaptation recommendations, practical testing, and consideration of the country's climatic and technical features. This approach ensured a comprehensive study and adaptation of standards for solar photovoltaic systems. Results: the research outcomes include identifying differences between international standards and Uzbekistan's national regulations, developing recommendations for their adaptation, considering the country's climatic and technical features. Adapting the standards will enhance the safety and reliability of photovoltaic systems, improve their testing and inspection processes, and support the national energy strategy, contributing to the increase of renewable energy sources’ share and the development of solar energy in Uzbekistan.